Survival and Recovery of Methanotrophic Bacteria Starved under Oxic and Anoxic Conditions - Roslev, Peter (1994)
The effects of carbon deprivation on survival of methanotrophic bacteria were compared in cultures incubated in the presence and absence of oxygen in the starvation medium. Survival and recovery of the examined methanotrophs were generally highest for cultures starved under anoxic conditions as indicated by poststarvation measurements of methane oxidation, tetrazolium salt reduction, plate counts, and protein synthesis. Methylosinus trichosporium OB3b survived up to 6 weeks of carbon deprivation under anoxic conditions while maintaining a physiological state that allowed relatively rapid (hours) methane oxidation after substrate addition. A small fraction of cells starved under oxic and anoxic conditions (4 and 10%, respectively) survived more than 10 weeks but required several days for recovery on plates and in liquid medium. A non-spore-forming methanotroph, strain WP 12, displayed 36 to 118% of its initial methane oxidation capacity after 5 days of carbon deprivation. Oxidation rates varied with growth history prior to the experiments as well as with starvation conditions. Strain WP 12 starved under anoxic conditions showed up to 90% higher methane oxidation activity and 46% higher protein production after starvation than did cultures starved under oxic conditions. Only minor changes in biomass and morphology were seen for methanotrophic bacteria starved under anoxic conditions. In contrast, starvation under oxic conditions resulted in morphology changes and an initial 28 to 35% loss of cell protein. These data suggest that methanotrophic bacteria can survive carbon deprivation under anoxic conditions by using maintenance energy derived solely from an anaerobic endogenous metabolism. This capability could partly explain a significant potential for methane oxidation in environments not continuously supporting aerobic methanotrophic growth.